Editors’ Introduction. Theodor W. Adorno: Between Critical Receptivity and Spontaneous Openness - Gandesha, Samir; Hartle, Johan; Hofstätter, Antonia; Lie, Han-Gyeol; Marino, Stefano (Journal of Adorno Studies, 2025)